STRATEGI KOMUNIKASI DINAS KEBUDAYAAN PARIWISATA PEMUDA DAN OLAHRAGA DALAM MEMPROMOSIKAN OBJEK WISATA PULAU JEMUR DI ROKAN HILIR - Pras Tiono; Rusmadi Awza (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
Jemur island is one of the attractions that will become a mainstay in Rokan Hilir. Tourist attraction is under the management of the Department of Tourism Culture Youth and Sports Rokan Hilir Riau province, which is responsible for introducing to the local tourists and foreign tourists. Beautiful scenery, as well as a typical phenomenon which is owned attractions such as websites that contain historical value that can be inviting tourists to come to the tourist attraction. But in reality attraction drying Jemur Island visit not too many tourists. The authors are interested in examining how the communication strategy undertaken Department of Tourism Culture Youth and Sports Rokan Hilir. The purpose of this study was to determine the communication strategy used Department of Tourism Culture Youth and Sports Rokan Hilir in promoting attraction Jemur and messaging strategies and the use of media in the promotion. This research uses qualitative descriptive method and data collection techniques that can be sorted by the fact the field is through observation, interviews, and documentation.Informantn in this study were 12 people who were taken bypurposive sampling method.Interactive Data Analysis Model writersuse to describe the results of research in data analysis techniques, and for examination ofthe validity of the data the researchers used a technique extension of participation as well as triangulation. The results showed that the communications strategy undertaken by the Department of Tourism Culture Youth and Sports Rokan Hilir not maximized. The communication strategy undertaken in the form, cooperated with the agency derah and outside the region inparticipating in various events as well as assistance in meeting the tourism support facilities, brochures, billboards, website. Factors affecting split into supporting factorssuch as: openness, availability of infrastructure, cooperation is compact, good relationswith the media and the private sector, technological advances.Then inhibiting factors,such as limited funds and support from the local community is still lacking. Keyword: Communication Strategy, Promotion, Jemur Island